1990
DOI: 10.1002/jemt.1060150304
|View full text |Cite
|
Sign up to set email alerts
|

Autoradiographic studies of selective amino acid uptake by neural and nonneural elements in the gerbil cochlea

Abstract: The cochlea is well suited for studies of the uptake properties of auditory neurons and nonneuronal supporting cells. Probe concentrations of radioisotopically labeled amino acids, including putative neurotransmitters and their precursors, breakdown products, and blockers, can be introduced via the natural, fluid-filled channels of the inner ear. Uptake patterns can be mapped at cellular and intracellular levels using light and electron microscopic autoradiographic methods. The procedures for introduction of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Immunoreactivity is also seen within the LSO as puncta, usually interpreted as terminals of MNTB neurons, surrounding the LSO principal cells (Campistron et al, 1986;Peyret et al, 1987;Wenthold et al, 1987;Aoki et al, 1988;Saint Marie et al, 1989). These bouton endings also show an affinity for >H-glycine (Schwartz, 1985). Glycine receptors can be identified on LSO principal cells using either a monoclonal antibody or jH-strychnine as a ligand (Zarbin et al, 1981;Frostholm and Rotter, 1985;Altschuler et al, 1986;Baker et al, 1986;.…”
Section: Overview Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunoreactivity is also seen within the LSO as puncta, usually interpreted as terminals of MNTB neurons, surrounding the LSO principal cells (Campistron et al, 1986;Peyret et al, 1987;Wenthold et al, 1987;Aoki et al, 1988;Saint Marie et al, 1989). These bouton endings also show an affinity for >H-glycine (Schwartz, 1985). Glycine receptors can be identified on LSO principal cells using either a monoclonal antibody or jH-strychnine as a ligand (Zarbin et al, 1981;Frostholm and Rotter, 1985;Altschuler et al, 1986;Baker et al, 1986;.…”
Section: Overview Of Resultsmentioning
confidence: 99%
“…Recently, studies have focused attention on the possible neurotransmitters in the superior olive. Histochemical and electrophysiological data suggest that MNTB neurons employ glytine as an inhibitory neurotransmitter in the circuit between MNTB and LSO (Zarbin et al, 198 1;Moore and Caspary, 1983;Caspary et al, 1985;Schwartz, 1985;Glendenning and Baker, 1988;Saint Marie et al, 1989). Our own previous study of the mouse brain slice has shown that glycine mediates contralateral IPSPs in LSO through neurons in MNTB (Wu and Kelly,199 1).…”
mentioning
confidence: 99%
“…Efferent fibres enter the organ in the olivocochlear bundle and consist of two fibre systems: (1) the lateral system, deriving from the complex of the lateral superior olive and participating in the innervation of the inner spiral bundle and plexus and (2) the medial system, originating near the medial superior olivary complex and innervating the outer hair cells (Wart & Guinan, 1979;Guinan et al, 1983;White & Warr, 1983). Retrograde transport of radioactive GABA from the cochlea (for review see Schwartz & Ryan, 1989) can be traced no further than to the floor of the fourth ventricle. The injection of nipecotic acid (NIP), a slowly metabolizing GABA analog, labelled neuronal perikarya in the regions of midbrain corresponding to the nuclei of origin of the medial olivocochlear system.…”
Section: Introductionmentioning
confidence: 99%